Combined IFN-α and 5-FU treatment as a postoperative adjuvant following surgery for hepatocellular carcinoma with portal venous tumor thrombus - NAGANO, HIROAKI (D.A. Spandidos, 2013)
The efficacy of combination therapy with subcutaneous interferon (IFN)-α and intra-arterial 5-fluorouracil (5-FU) as a postoperative adjuvant for resectable advanced hepatocellular carcinoma (HCC) invading the major branches of the portal vein (PVTT) was examined. The prognosis of HCC with PVTT (Vp3 or 4) is extremely poor. Recently, we reported the possibility of combination therapy with IFN-α and intra-arterial 5-FU for intractable HCC with PVTT as a postoperative adjuvant and this is the second report. Patients with HCC with PVTT were included (n=50). Thirty consecutive patients with HCC and PVTT were treated with 3 cycles of a combination therapy consisting of arterial 5-FU infusion (300 mg/mm(3)/day, 5 days/week, for the initial 2 weeks) and IFN subcutaneous injection (5 MIU, 3 times/week, 4 weeks) as a postoperative adjuvant following hepatic resection; another 20 patients receiving no IFN/5-FU chemotherapy acted as controls. Results for the IFN/5-FU adjuvant treatment group were as follows: disease-free survival (n=9, 15–109 months), survival with recurrence (n=6, 30–92 months), cancer death (n=9, 14–60 months), death from other causes but no recurrence (n=5, 13–87 months) and death from other causes with recurrence (n=1, 22 months). The 1-year survival rate was 100% in patients treated with IFN/5-FU, and 30% in those without IFN/5-FU as historical controls (n=20). There was a significant difference in disease-free and overall survival rates between the two groups (P<0.0001). In conclusion, IFN/5-FU combination therapy may be a very promising postoperative adjuvant treatment for HCC with PVTT.